Video Attributes in Teaching and Learning: A Systematic Review - Mohd Nasir, Muhammad Nuqman; Masek, Alias; Razali, Siti Soleha; Rosman, Nur Liyana; Ismail, Affero (Journal of TVET and Technology Review, 2023)
This study was conducted to establish guidelines for video attributes for electrical subjects. Based on previous research, researchers have found several elements that must be present in the process of preparing video attributes. Data analysis conducted by the researchers found a total of 12 related papers from 32 sources of search. The results of the observations carried out by the researchers found that the elements that need to be in the preparation of the video are text, animation, movement, segmentation, and some related ones, as stated in the finding section.